How do paediatricians use and monitor antithyroid drugs in the UK? A clinician survey. (17th June 2019) - Lawrence, Neil; Cheetham, Tim; Elder, Charlotte
Abstract: Objective: We aimed to document current practice in the medical management of paediatric hyperthyroidism in the UK and compare to international recommendations. Design: A 27‐question online survey distributed via an electronic newsletter in August 2018. Participants: Responses from 48 members (11%) of the British Society for Paediatric Endocrinology and Diabetes. Measurements: Information about antithyroid drug (ATD) preference, treatment duration, monitoring of full blood count (FBC), management of neutropaenia, agranulocytosis screening and patient education. Results: Carbimazole is favoured by 98% of respondents and a "dose titration" regimen preferred over "block and replace" (65% vs 29%). TRAbs (thyroid‐stimulating hormone receptor antibodies) are used for diagnostic purposes by 85% and by 33% to look for evidence of disease remission. The majority (81%) treat for a minimum of 2 years before considering a trial off ATD. All respondents reported that they "always/usually" warn their patients about the risk of agranulocytosis before starting ATD, but written information is "rarely/never" provided by 63%. Sore throat (98%) and fever (92%) are the most commonly cited symptoms used to alert a patient to possible agranulocytosis. FBC is measured prior to treatment by 65% and measured periodically during treatment by 70%. Conclusions: The management of paediatric hyperthyroidism with ATDs in the UK is not consistent with all international recommendations because a block and replace ATD regimen remains widely used. TRAbs are utilized at presentation, but underused for detecting disease remission. National consensus guidelines and written patient information may refine the management of paediatric patients on ATDs.